2004
DOI: 10.1161/01.hyp.0000124667.34652.1a
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Angiotensin-Converting Enzyme 2 After Myocardial Infarction by Blockade of Angiotensin II Receptors

Abstract: Abstract-We investigated in Lewis normotensive rats the effect of coronary artery ligation on the expression of cardiac angiotensin-converting enzymes (ACE and ACE 2) and angiotensin II type-1 receptors (AT 1a -R) 28 days after myocardial infarction. Losartan, olmesartan, or the vehicle (isotonic saline) was administered via osmotic minipumps for 28 days after coronary artery ligation or sham operation. Coronary artery ligation caused left ventricular dysfunction and cardiac hypertrophy. These changes were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
491
5
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 545 publications
(529 citation statements)
references
References 43 publications
20
491
5
13
Order By: Relevance
“…In addition, mice deficient in both ACE and ACE2 show completely normal heart function [25]. Thus ACE and ACE2 are thought to negatively regulate each other [26][27][28][29]. However, at this point, the full role of ACE2 in vivo and its impact on differences in response to ACE inhibitors and ARBs in women compared to men with CHF remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mice deficient in both ACE and ACE2 show completely normal heart function [25]. Thus ACE and ACE2 are thought to negatively regulate each other [26][27][28][29]. However, at this point, the full role of ACE2 in vivo and its impact on differences in response to ACE inhibitors and ARBs in women compared to men with CHF remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, chronic Ang-(1-7) treatment not only attenuated the development of heart failure in response to coronary artery ligation in rats (Loot et al 2002), but it also reversed cardiac hypertrophy and fibrosis in rats (Iwata et al 2005;Tallant et al 2005;Wang et al 2005;Grobe et al 2006a;2006b). Ishiyama et al (2004) found that heart failure induced by coronary artery ligation was associated with an increase in plasma Ang-(1-7) levels, which was augmented with the administration of the AT 1 receptor blockers losartan and olmesartan. The AT 1 -receptor blockade was associated with an upregulation of cardiac ACE2, suggesting that the increased Ang-(1-7) levels may be due to increased ACE2.…”
Section: Aj Trask and CM Ferrariomentioning
confidence: 99%
“…Whether the effects of several ARBs on ACE2 expression are same remains uncertain [10][11][12] especially in hypertensive patients. The present finding that the plasma Ang II level was decreased after replacement of candesartan with olmesartan without any changes in PRC suggests that the effect of olmesartan on ACE2 expression is more stimulating than that of candesartan.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Takeda et al 10 reported that treatment with candesartan increased ACE2 mRNA level and decreased angiotensinogen mRNA level in the heart. Recently, it was shown that olmesartan increased ACE2 expression during the remodeling of the heart after myocardial infarction, 11 and olmesartan improved left ventricular remodeling with an increase in cardiac ACE2 expression in stroke-prone spontaneously hypertensive rats. 12 The ACE2 is a membrane-associated carboxy-peptidase that is highly expressed in the heart and kidney 13 and hydrolyzes Ang II to Ang 1-7, which inhibits the ACE C-domain and bradykinin by acting as an ACE inhibitor.…”
mentioning
confidence: 99%